Synaptic cell adhesion molecules contribute to the pathogenesis and progression of fragile X syndrome - Bai, Shu-Yuan; Zeng, De-Yang; Ouyang, Ming; Zeng, Yan; Tan, Wei; Xu, Lang (Frontiers in Cellular Neuroscience, 2024)
Fragile X syndrome (FXS) is the most common form of inherited intellectual disability and a monogenic cause of autism spectrum disorders. Deficiencies in the fragile X messenger ribonucleoprotein, encoded by the FMR1 gene, lead to various anatomical and pathophysiological abnormalities and behavioral deficits, such as spine dysmorphogenesis and learning and memory impairments. Synaptic cell adhesion molecules (CAMs) play crucial roles in synapse formation and neural signal transmission by promoting the formation of new synaptic contacts, accurately organizing presynaptic and postsynaptic protein complexes, and ensuring the accuracy of signal transmission. Recent studies have implicated synaptic CAMs such as the immunoglobulin superfamily, N-cadherin, leucine-rich repeat proteins, and neuroligin-1 in the pathogenesis of FXS and found that they contribute to defects in dendritic spines and synaptic plasticity in FXS animal models. This review systematically summarizes the biological associations between nine representative synaptic CAMs and FMRP, as well as the functional consequences of the interaction, to provide new insights into the mechanisms of abnormal synaptic development in FXS.